Research on women`s football: a scoping review - Kryger, K. O.; Wang, A.; Mehta, R.; Impellizzeri, F. M.; Massey, A.; McCall, A. (Science and Medicine in Football, 2022)
Aim: This study aims to scope available peer-reviewed literature published in a FIFA language to understand the current quantity of research on women`s football. Methods: Five databases were searched on the 15/12/2019. Studies were included when containing original research published in a peer-reviewed journal around female competitive football of any level, any age and on any subject. Author, journal, title and abstract of all included studies were scoped. Population assessed number of participants, level of play, age level of football and publication theme(s) were extracted. Results: A total of 1,634 articles were scoped. The oldest publication dated back to 1939, whilst a total of 202 studies were gathered from 2019. The publication theme most frequently researched was sports medicine (N = 521) followed by strength and conditioning (N = 331) and sociology (N = 299). The majority of studies has focussed on elite (N = 442), senior (N = 977) players. Conclusion: A continuous growth in research attention has been seen. However, the numbers are not comparable to current research output levels in men`s football. This study represents an essential first step in a larger `research agenda-setting` project to determine research priorities for women`s football during the next 10 years.